2016
DOI: 10.14814/phy2.12866
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)‐1 in rat parturition: IL‐1 receptors 1 and 2 and accessory proteins abundance in pregnant rat uterus at term – regulation by progesterone

Abstract: The role of interleukin‐1 (IL‐1), a pro‐inflammatory cytokine, in parturition is typically noted by changes in its concentrations. Studying the expression of its receptor family, IL‐1 receptor (IL‐1R) 1, IL‐1R2, IL‐1R accessory protein (IL‐1RAcP), and its predominantly brain isoform, IL‐1RAcPb, during late gestation in the uterus in the Long‐Evans rat is another. We assessed changes in their mRNA and protein relative abundance in the uterus and compared IL‐1RAcP and IL‐1RAcPb mRNA abundance in uterus, cervix, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…Additionally, although the experience of stress is inherent to life and pregnancy, a single stressor is hardly representative of day-to-day life. Moreover, while PTB can be induced in mice by exposure to endotoxins or IL-1β alone [21], this is not the case in rats [51]. The latter is in accordance with the cumulative stress or multiple-hit hypothesis [60,61] and the concept of allostatic load [18,62,63].…”
Section: Models Of Cumulative Stressmentioning
confidence: 60%
See 1 more Smart Citation
“…Additionally, although the experience of stress is inherent to life and pregnancy, a single stressor is hardly representative of day-to-day life. Moreover, while PTB can be induced in mice by exposure to endotoxins or IL-1β alone [21], this is not the case in rats [51]. The latter is in accordance with the cumulative stress or multiple-hit hypothesis [60,61] and the concept of allostatic load [18,62,63].…”
Section: Models Of Cumulative Stressmentioning
confidence: 60%
“…We also evaluated the expression of the gluco-and mineralocorticoid receptors, nuclear receptor subfamily 3 group c member 1 (Nr3c1) and 2 (Nr3c2), respectively, and both isoforms of 11β-hydroxysteroid dehydrogenase, Hsd11b1 and Hsd11b2 [50]. Furthermore, we analyzed the mRNA expression of the components of the IL-1 receptor complex, consisting of IL-1 receptors (Il1r1 and Il1r2) and receptor accessory proteins (Il1racp and Il1racpb) [51], as well as the mRNA abundance of pro-inflammatory cytokines interleukin-1 alpha (Il1a) and beta (Il1b) [21], interleukin-6 (Il6) [52], the endogenous IL-1 receptor antagonist (Il1rn also known as Il1ra) [53], and the anti-inflammatory interleukin-10 (Il10) [28,54]. An overview of the physiological roles of these genes and their respective proteins is available in Supplemental Table S1.…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…IL-1 receptor type I has been studied as one of the potential biomarkers to predict heart failure in hypertensive patients ( 52 ) and was proposed as a candidate molecular target for rheumatoid arthritis treatment ( 53 ). In the pregnancy space, IL-1R1 has been investigated in endometrial tissues and chorioamnionitis ( 54 , 55 ) and has been found to be increased in PTBs stimulated by RU486 in rats ( 56 ). One study found an aberrant placental expression of interleukin 1 receptor-like 1 ( IL-1RL1 ) in PTB cases (compared with spontaneous term births) whose mRNA transcript were of higher detection in maternal plasma samples than their gestational age-matched controls that had term birth, suggesting IL-1RL1 to be a candidate PTB-associated marker ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that a higher expression level of IL1RAP was associated with increased neutrophil counts in the airways of asthmatic patients, suggesting enhanced neutrophilic inflammation . The expression level of IL1RAP is likely associated with uterine sensitivity to IL‐1 during late gestation and delivery . IL1RAP is abnormally up‐regulated in the placentas of pregnant women with sickle cell anaemia [33].…”
Section: Discussionmentioning
confidence: 99%
“…31 The expression level of IL1RAP is likely associated with uterine sensitivity to IL-1 during late gestation and delivery. 32 IL1RAP is abnormally upregulated in the placentas of pregnant women with sickle cell anaemia [33]. Sickle cell disease is often accompanied with acute and chronic inflammation [33].…”
Section: Injection Of Mmu-mir-19a-3p Reversed the Mir-19a-3p Expressionmentioning
confidence: 99%